Herbaceous cotton yield in no-till system in rainfed Savannah conditions with crop rotation - Corrêa, José Carlos; Sharma, Ravi Datt (Pesquisa Agropecuaria Brasileira, 2004)
The experiment was carried out in a heavy red yellow latosol and aimed at evaluating crop rotation on herbaceous cotton yields in no-till system under rainfed Savannah conditions. The experimental design used was a completely randomised blocks with five treatments: soybean-millet-soybean-millet-cotton; soybean-amaranth-soybean-forage radish-soybean-cotton; soybean-grain sorghum-soybean-grain sorghum-cotton; soybean-black rye-soybean-black rye-cotton and soybean-soybean-cotton and four replications. The highest cotton seed yield was obtained in the sequence soybean-millet-soybean-millet-cotton, in which best weed control also occurred.